Pelatihan Pembuatan Karya Ilmiah bagi Guru Kementerian Agama Kabupaten Karanganyar - Ulfah, Yetty Faridatul; Khasanah, Uswatun; Fatchurrohman, Mukhlis; Muslimah, Eva; Nurhanifa, Faurina (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Teachers are very influential on improving the quality of national education. In addition to teaching in the classroom, a teacher should develop competencies that also aim for self-development. One of the ways for teachers to develop their abilities and competencies is to take part in scientific writing training. This article aims to recognize the attitudes and responses of the teachers of the Ministry of Religion of Karanganyar Regency in the State Islamic Primary School and Muhammadiyah Primary School. The result of this training is that the teachers are quite responsive and enthusiastic about the holding of this scientific writing training. In addition, there are about 20 teachers who are finally able to continue with more in-depth research considering that they had made a good framework in writing.